A Literature Review on the Effect of Perceived Organizational Support on Employee Engagement and Employee Performance of Government Agencies in Singapore, Thailand and Indonesia - Rahmadani, Rahmadani; Rahim, Abdul Rahman; Prasilowati, Sri Lestari; Siradjuddin, Siradjuddin (Ridwan Institute, 2024)
The support of the organization where individuals work influences employees' quality of life in government agencies. Employee-perceived organizational support (POS) has been proven in previous research to help reduce employee stress levels and emotional exhaustion during work. The influence of POS in government agencies in Singapore, Thailand, and Indonesia shows similarities and differences. This research explores POS elements, namely Socio-emotional, Orientation towards organization and work, Behavioral outcomes, and Employee welfare, and its impact on government agencies in Singapore, Thailand, and Indonesia. The author uses a qualitative literature study approach; this research reveals POS elements practiced in government agencies in Singapore, Thailand, and Indonesia. The three countries theoretically use POS elements. However, in practice, their impact is very different, so the results of engagement and performance produced by employees are also different. The difference is that the POS implemented in Singapore and Thailand agencies contains a